The Effectiveness of Implementing COVID-19 Nursing Practice Guidelines in the Emerging Infectious Disease Critical Care Unit at Sakon Nakhon Hospital - Sirimontri, Jeerawan; Hunghuan , Kanitta; Daekhunthod , Tasanee (Medical Journal of Sakon Nakhon Hospital, 2024)
This quasi-experimental research aimed to evaluate the effectiveness of COVID-19 critical care nursing practice guidelines in the Emerging Infectious Disease Critical Care Unit at Sakon Nakhon Hospital and to assess nurses’ satisfaction with these guidelines. The sample consisted of 13 registered nurses and 40 COVID-19 critical patients, divided into pre- and post-implementation groups of 20 patients each. The research instruments consisted of COVID-19 critical care nursing practice guidelines, nursing activity checklist, and satisfaction assessment form. All three instruments were validated with a Content Validity Index (CVI) of 0.80. Reliability was analyzed using the Cronbach’s alpha coefficient; the nursing activity checklist had a reliability of 0.85, and the satisfaction assessment form had a reliability of 0.87. Data were analyzed using descriptive statistics and Chi-square test. The results showed that 1) after implementing the guidelines, the incidence of complications in patients decreased significantly (p < .05), including severe sepsis (from 20% to 5%), acute kidney injury (from 20% to 10%), mortality rate (from 10% to 5%) and acute respiratory failure (from 10% to 5%) and 2) the registered nurses had the highest level of satisfaction with the guidelines (Mean = 4.38, S.D = 0.51). These findings demonstrate that the guidelines were effective in reducing complications and well-accepted by practitioners.